Pengaruh Motivasi dan Inovasi Terhadap Pemanfaatan Media Sosial Sebagai Alat Pembelajaran IPTEK di Kalangan Mahasiswa Manajemen - Mutia Anggraeni; Giantoro Pamungkas; Dwi Yuliyanti Fitri; Fina Ikfini Maulaya; Putri Mardiana; Tubagus Faliyan Maulana (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Abstract, This study aims to evaluate the impact of motivation and innovation on the use of social media as a learning tool in the field of Science and Technology (IPTEK) among students of the Management Study Program. Social media is now a crucial platform in supporting digital learning, facilitating students to access information and collaborate more interactively. The data used in the study were obtained through filling out a questionnaire by 50 randomly selected management students. Analysis of the results shows that students' intrinsic motivation, such as the drive to learn independently, and extrinsic motivation, such as recognition from peers, have a significant positive correlation with the use of social media for learning purposes. Not only that, the aspect of innovation in the use of social media, such as exploring interactive features such as online discussions and sharing educational content, also strengthens this positive impact. This study suggests that motivation and innovation play an important role in increasing the effectiveness of learning through social media, so it is advisable to emphasize this approach more in designing higher education curricula.